IMPROVING ENGLISH FOR NURSING COMMUNICATION SKILLS THROUGH SCENARIO-BASED LEARNING (SBL) IN EMERGENCY CARE - SB, Handayani; Ramadhan, Syahrul; Tiarina, Yuli (Universitas PGRI Sumatera Barat, 2025)
Scenario-based learning (SBL) is a teaching method that uses real-life simulations to help students develop practical skills and apply their knowledge in relevant and realistic contexts. This study aims to explore the impact of implementing scenario-based learning in English for Nursing, with a focus on improving students’ communication skills. The research used a qualitative approach, conducting in-depth interviews with 41 students from Akper Kesdam I/Bukit Barisan Padang who had participated in scenario-based learning. Data were collected to identify changes in students’ confidence, language anxiety, and their ability to apply medical communication in real-world situations. The findings indicate that scenario-based learning significantly improved students’ confidence in using English for communication, reduced language anxiety, and deepened their understanding of the importance of clear communication in emergencies. The scenarios provided practical experience that helped students bridge theory with real-life applications, better preparing them for urgent medical situations. Based on these findings, it can be concluded that integrating scenario-based learning into English for Nursing is effective in preparing nursing students to address communication challenges in medical settings and in improving patient care quality.